The Influence of Company Image and Customer Experience on Satisfaction and the Impact on Repurchase Intention - Putri Febriyani Aldriyanti; Endang Tjajaningsih (Program Studi Manajemen, Fakultas Ekonomi, Universitas Langlangbuana, 2022)
The growth of coffee shops in Indonesia is increasing, and the number of enthusiasts in the coffee world is increasing. With so many new coffee shops being established, many innovations have also been created. To get customer satisfaction and the occurrence of repurchase intentions from many customers' perceptions of how the company's image and experience are from their purchases. The research objective is to determine the effect of corporate image and customer experience on the desire to repurchase the customer. a technique used by using the purposive sampling method. The sample size is 100 respondents distributing questionnaires which are measured using a Likert scale. The analysis used is a path analysis technique using multiple linear regression tests, t-tests, and F tests. Company image has a positive and significant effect on customer satisfaction, customer experience has a positive and significant effect on customer satisfaction. Company image has a positive and significant effect on repurchase intention. customer experience does not affect repurchase intention. a customer has a positive and significant effect on repurchase intention